The Histological of Ewe Ovarium Post-Intrauterine Transplantation to Pseudopregnancy Rabbit - Sumarmin, R; Boediono, A; Winarto, A; Yusuf, TL (ANIMAL PRODUCTION, 2008)
The objective of this study was to evaluate the histologycal of ewe ovarium post-intrauterin transplantation to pseudopregnancy rabbit. The experiment was concerned with the 1 or 7 days of pseudopregnancy to receive the ewe ovarian transplant. Post transplantation 5, 7 or 9 days of ewe ovarium were recollected. To determine histologically post-intrauterine transplantation of ewe ovarium, the histological preparat was prepared by the paraffin methods followed by HE staining. The result showed that there were follicle development with all stages of follicle dynamics (Primordial, Primary, Prentral and Antral follicle stages) in all group of treatment. The ewe ovarian post-intrauterine transplantation damaged was found as follicles degeneration, ephitellial damaged and the formation of protein aggregate. It can be concluded that the histological of ewe ovarium post-intrauterine transplantation in pseudopregnancy rabbit is still good in the 5 or 7 days after intrauterine transplantation in pseudopregnancy rabbit. (Animal Production 10(2): 78-84 (2008)Â Key Words: Histological,Â  post-intrauterine transplantation, ewe ovarium